2022
DOI: 10.1080/21655979.2022.2060776
|View full text |Cite
|
Sign up to set email alerts
|

circHIPK3 regulates cell proliferation and migration by sponging microRNA-124 and regulating serine/threonine kinase 3 expression in esophageal squamous cell carcinoma

Abstract: Circular RNAs (circRNAs) are a type of important non-coding RNAs that widely involve in the physiological and pathophysiological process. Recent research has established a link between circHIPK3 and the malignant activity of cancer cells. However, circHIPK3’ role in esophageal squamous cell carcinoma (ESCC) still needs more focus. To determine the prognostic value of circHIPK3 in patients with ESCC, the expression of circHIPK3 was quantified in 32 pairs of ESCC using real-time polymerase chain reaction (RT-qPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Mechanistically, circHIPK3 was identified to promote ESCC development through the miR-599/c-MYC axis 71 . Besides, Yao et al found that circHIPK3 facilitated AKT serine/threonine kinase 3 (AKT3) expression by sponging miR-124, thus forming the circHIPK3/miR-124/AKT3 axis to promote ESCC cell proliferation, migration, and epithelial-mesenchymal transition 72 .…”
Section: The Dual Roles Of Circhipk3mentioning
confidence: 99%
“…Mechanistically, circHIPK3 was identified to promote ESCC development through the miR-599/c-MYC axis 71 . Besides, Yao et al found that circHIPK3 facilitated AKT serine/threonine kinase 3 (AKT3) expression by sponging miR-124, thus forming the circHIPK3/miR-124/AKT3 axis to promote ESCC cell proliferation, migration, and epithelial-mesenchymal transition 72 .…”
Section: The Dual Roles Of Circhipk3mentioning
confidence: 99%
“…In this study, we systematically analyzed the expression level and correlation of NRGs in HBV-HCC and paracarcinoma tissues. Gene ontology analysis revealed 24 DENRGs that were enriched for pathways related to the proliferation and migration of tumor cells ( 17 , 18 ). In addition to HBV-HCC tissues, LGALS3 expression was also upregulated in CHI tissues and tissues with high fibrosis scores.…”
Section: Discussionmentioning
confidence: 99%
“…Yao et al reported that an elevated level of circHIKP3 in ESCC cells remarkably absorbed miR-599 expression and significantly stimulated c-MYC expression, leading to cell growth and metastasis [ 33 ]. Yao and colleagues validated that miR-124 functioned as the sponged miRNA in this case and serine/threonine kinase 3 (AKT3) was enhanced under the modulation of circHIPK3, which further triggered ESCC cell growth and metastasis [ 34 ].…”
Section: The Role Of Circhipk3 In Human Cancersmentioning
confidence: 99%